A randomized clinical trial of the efficacy and safety of sitagliptin as initial oral therapy in youth with type 2 diabetes. Issue 2 (22nd December 2021) - Shankar, R. Ravi; Zeitler, Philip; Deeb, Asma; Jalaludin, Muhammad Yazid; Garcia, Raymundo; Newfield, Ron S.; Samoilova, Yulia; Rosario, Carmen A.; Shehadeh, Naim; Saha, Chandan K.; Zhang, Yilong; Zilli, Martina; et al.
Abstract: Objective: To assess the efficacy and safety of DPP‐4 inhibition with sitagliptin in youth with type 2 diabetes (T2D). Study Design: This was a 54‐week, double‐blind, randomized, controlled clinical trial evaluating the safety and efficacy of DPP‐4 inhibition with sitagliptin 100 mg once daily as initial oral therapy in youth with T2D. The 190 participants, aged 10–17 years, had HbA1c 6.5%–10% (7.0%–10% if on insulin). All were negative for pancreatic autoantibodies and overweight/obese at screening or diagnosis. The trial was placebo controlled for the first 20 weeks, after which metformin replaced placebo. The primary efficacy endpoint was change from baseline in HbA1c at Week 20. Results: Treatment groups were well balanced at baseline (mean ± SD HbA1c = 7.5% ± 1.0, BMI percentile = 97.1% ± 6.8, age = 14.0 years ± 2.0 [57.4% <15], 60.5% female). At Week 20, least squares mean changes from baseline in HbA1c were −0.01% (sitagliptin) and 0.18% (placebo); between‐group difference (95% CI) = −0.19% (−0.68, 0.30), p = 0.448. At Week 54, the changes in HbA1c were 0.45% (sitagliptin) and −0.11 (placebo/metformin). There were no notable between‐group differences in the adverse event profiles through Week 54. Conclusions: DPP‐4 inhibition with sitagliptin did not provide significant improvement in glycemic control. In this study, sitagliptin was generally well tolerated with a safety profile similar to that reported in adults. (ClinicalTrials.gov: NCT01485614; EudraCT: 2011‐002528‐42)